(untitled) (European Journal of Health Research, 2020)
This non-experimental transactional descriptive research aims to determine the sociodemographic, sexuality and pregnancy indicators in 88 mothers belonging to prevention programs of the Colombian Family Welfare Institute (ICBF) Centro Zonal Norte. For the data collection, a sociodemographic record prepared by the researchers was used, taking into account guidelines from other works. The analysis was carried out through the statistical software SPSS version 25 and the Chi-Square statistic was used to obtain the frequency and percentage. All the regulations established by the criteria of resolution 8430/93, issued by the Ministry of Health of Colombia, and Law 1090 of the Psychologist were followed. The results show that sociodemographic and sexuality indicators associated with teenage pregnancy are: early pregnancy, low schooling, low socioeconomic status, non-use of contraceptive methods, unplanned pregnancy.